KLITIH: IMPLIKASI HUKUM BAGI ANAK DI YOGYAKARTA - Bangun, Jeremy Arnold Christian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The crime of klitih, involving youth groups committing random acts of violence in Yogyakarta, has become a critical issue requiring attention from both the public and law enforcement authorities. This crime poses a potential threat to public order and societal safety. This study aims to analyze the legal implications arising from klitih offenses committed by minors, with a focus on the applicable regulations and the manner in which the judicial system addresses such cases. The research employs a normative legal method with a descriptive approach, using qualitative analysis of secondary data. The findings indicate that a more rehabilitative and child protection-oriented legal approach is essential in addressing juvenile offenses of klitih. Accordingly, the study provides recommendations for the development of more effective legal policies to prevent criminal behavior among minors and support the reintegration of juvenile offenders into society.Keywords: Klitih, Juvenile Offenses, Legal Implications, Child Rehabilitation, Public Security